2017
DOI: 10.1002/jgf2.52
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation by the Basic Checklist and the risk of 3 years incident long‐term care insurance certification

Abstract: BackgroundA rapidly aging society needs effective approaches to support frail older people who have a high risk of requiring long‐term care. We investigated the validity of the Basic Checklist (the “Kihon Checklist”) as a tool to select candidates for a program to prevent long‐term care.MethodA survey with questions from the Basic Checklist was conducted with functionally independent older residents aged ≥65 years living in Takasaki City, Japan. Subjects who completed the questionnaire were followed over 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…Also, despite the well‐known capability of health checkups to reduce mortality, their efficacy for preventing long‐term care dependence in older adults has not been elucidated . Furthermore, the substantial characteristics of “hard‐to‐reach” older residents who did not participate in these health promotions could not be conjectured from the results of the above studies, as all the older adults enrolled in these studies, including even “non‐participants” in health checkups, were actually responders to invitations in field, outpatient clinic, postal, and home‐visit health‐promotion surveys.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, despite the well‐known capability of health checkups to reduce mortality, their efficacy for preventing long‐term care dependence in older adults has not been elucidated . Furthermore, the substantial characteristics of “hard‐to‐reach” older residents who did not participate in these health promotions could not be conjectured from the results of the above studies, as all the older adults enrolled in these studies, including even “non‐participants” in health checkups, were actually responders to invitations in field, outpatient clinic, postal, and home‐visit health‐promotion surveys.…”
Section: Introductionmentioning
confidence: 99%
“…The Kihon Checklist (KCL), a postal self‐reporting yes/no questionnaire survey consisting of simple 25‐item assessments, which has been shown to be an excellent tool for screening frailty status in older adults and for predicting support/care‐need certification, which was introduced in 2006, was mailed with the aim of reaching all uncertified older residents by municipalities from 2008. Secondary preventive care programs provided by municipalities to frail older adults were discontinued in 2015, because of the low participation rate in these programs, being 0.8% of total older adults in Japan and 1.7% in U‐town in 2011, compared with the objective of 5% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A 1-year follow-up study found that AD patients who scored <16 on the Mini-Mental State Examination tended to have ADL disabilities 1 year later. 4 In this context, we focused on individuals with mild-to-moderate AD (mean Mini-Mental State Examination score 20.0 AE 3.5) and scores of ≥97.9 points (out of 100) on the Barthel Index. Therefore, a longer than 1-year follow-up period seemed to be required to increase the statistical power of the Letters to the Editor -Comments © 2020 Japan Geriatrics Society | 263…”
Section: Department Of Hygiene and Public Health Nippon Medicalmentioning
confidence: 99%
“…Finally, Kamegaya et al . carried out a 3‐year prospective study for detecting care requirement by KCL subscales . Adjusted odds ratios (95% confidence interval) of physical dysfunction, poor nutritional condition, oral dysfunction, homebound state, dementia and depression for subsequent care requirement were 2.29 (2.05–2.55), 1.85 (1.38–2.48), 1.40 (1.25–1.57), 1.91 (1.55–2.37), 1.97 (1.75–2.20) and 1.96 (1.73–2.22), respectively.…”
mentioning
confidence: 99%